Walter Humes Keynote: Re-shaping the map of Educational Studies: Lessons from Dewey's Democracy and Education - Walter Humes (University of Aberdeen, School of Education, 2017)
The argument of this paper falls into four parts. In the first, an attempt is made to identify the essential characteristics of Democracy and Education, first published in 1916, which help us to understand the reasons for its success. This serves as a reference point for subsequent discussion. The second section jumps forward in time and examines debates in the 1960s and beyond about the nature of educational studies, noting points of similarity to, and difference from, Dewey. This is followed, in the third part, by an illustration of how changes in the way educational studies are conceptualised have affected policy proposals, using two Scottish documents, one published in 1977, the other in 2004. In the final part, the question of where this leaves us now is addressed. What options are open to those who are concerned about the relationship between education and democracy? Is it possible to recapture something of Dewey's comprehensive vision or is that asking too much of a disciplinary field that has expanded, diversified and, in some respects, fractured? (Note: An earlier version of the paper was given at the 2016 conference on Democracy and Education held at the University of the West of Scotland.)